IL-33/ST2 axis contributes to the dermal fibrosis of systemic sclerosis via promoting fibroblasts activation. Issue 2 (August 2022) - Wu, Xuefen; Ming, Bingxia; Wu, Tong; Gao, Rongfen; Hu, Peng; Tang, Jungen; Zhong, Jixin; Zheng, Fang; Dong, Lingli
Abstract: Background: Systemic sclerosis (SSc) is a chronic immune-mediated rheumatic disease that is characterized by fibrosis of the skin and internal organs. Interleukin-33 (IL-33) has been recently implicated in several autoimmune diseases through its receptor ST2. Objective: The aim of this study was to investigate the role and underlying mechanism of IL-33/ST2 axis in the fibrotic disorder of SSc. Methods: The bleomycin (BLM)-induced fibrotic skin and skin biopsies of SSc patients were used to detect the expression of IL-33 and ST2. Human dermal fibroblasts were stimulated with recombinant IL-33(rIL-33) protein and their activation, proliferation and migration were assessed. The role of IL-33/ST2 axis was investigated in mouse fibrosis model via histologically assessing skin fibrosis after IL-33 gene knockout. ST2 neutralizing antibody treatment was also obtained to estimate the possible effect. Results: The number IL-33 + cells and ST2 + cells were increased in the lesion skin of SSc patients and BLM-induced mouse. Human skin fibroblasts highly expressed ST2 protein, and the proliferation, migration, and collagen expression were significantly elevated after rIL-33 stimulation, accompanied by the activation of MAPKs and NF-kB pathways. The severity of skin fibrosis was significantly reduced in il33-/- mice compared with WT mice. Blockade of IL-33 receptor using an anti-ST2 neutralizing antibody effectively ameliorated the skin fibrosis. Conclusion: These data indicate that IL-33/ST2 axis contributes to the fibrotic skin injury of SSc via promoting fibroblasts activation, and IL-33/ST2 blockade might serve as a novel strategy to inhibit the fibrosis progression in patients of SSc. Highlights: Interleukin-33 promotes the fibrotic properties of fibroblasts. Interleukin-33 deficiency alleviated BLM-induced dermal fibrosis. Anti-ST2 antibody treatment ameliorated BLM-induced dermal fibrosis. Interleukin-33 have a direct influence on dermal fibroblasts.